Handbook of learning disabilities - Swanson, Lee H (The Guilford Press, 2013)
"This comprehensive handbook reviews the major theoretical, methodological, and instructional advances that have occurred in the field of learning disabilities. With contributions from leading researchers, the volume synthesizes a vast body of knowledge on the nature of learning disabilities, their relationship to basic psychological and brain processes, and how students with these difficulties can best be identified and treated. Findings are reviewed on ways to support student performance in specific skill areas/m-/including language arts, math, science, and social studies/m-/as well as general principles of effective instruction that cut across academic domains. Authoritative and up to date, the book also examines the concepts and methods that guide learning disability research and identifies promising directions for future investigation"--